Buckling of Rectangular Plates Under Discontinuous Loading Along Boundaries - Golec, J. (Engineering Transactions, 1976)
The paper deals with a problem of buckling of the elastic isotropic elastically homogeneous rectangular plates of small thickness, loaded arbitrarily along the boundaries, at the different boundary conditions assumed.The solution presented contains two stages, i.e., 1) the determination of the distribution of the internal forces in a shield subjected to the action of the arbitrary discontinuous load and 2) the computation of the critical parameters causing the plate buckling. In the first stage the finite Fourier transform was applied, whereas in the second stage the double Fourier series and Lardy's method were used to find solution to the plate buckling problem in two cases of boundary conditions of the plate: i.e., freely supported on the whole circumference and clamped along two opposite edges and freely supported on the remaining boundaries. In both considered cases the solution of the problem was reduced to the infinite linear homogeneous algebraic systems of equations.The results of computations which are of great practical significance are presented in the form of tables and figures which can immediately be used in engineering practice.